Hydrodynamic analysis of different thumb positions in swimming - Marinho, D. A.; Rouboa, A. I.; Alves, F. B.; Vilas-Boas, J. P.; Machado, L.; Reis, V. M.; Silva, A. J. (Journal of Sports Science & Medicine, 2009)
The aim of the present study was to analyze the hydrodynamic characteristics of a true model of a swimmer hand with the thumb in different positions using numerical simulation techniques. A three-dimensional domain was created to simulate the fluid flow around three models of a swimmer hand, with the thumb in different positions: thumb fully abducted, partially abducted, and adducted. These three hand models were obtained through computerized tomography scans of an Olympic swimmer hand. Steady-state computational fluid dynamics analyses were performed using the Fluent® code. The forces estimated in each of the three hand models were decomposed into drag and lift coefficients. Angles of attack of hand models of 0º, 45º and 90º, with a sweep back angle of 0º were used for the calculations. The results showed that the position with the thumb adducted presented slightly higher values of drag coefficient compared with thumb abducted positions. Moreover, the position with the thumb fully abducted allowed increasing the lift coefficient of the hand at angles of attack of 0º and 45º. These results suggested that, for hand models in which the lift force can play an important role, the abduction of the thumb may be better, whereas at higher angles of attack, in which the drag force is dominant, the adduction of the thumb may be preferable.